CHILDHOOD EMOTIONAL ABUSE AND ITS IMPACT ON HAPPINESS AND COPING STRATEGIES AMONG YOUNG ADULTS IN UNIMAS - Syaza Salma Sarahah, Salihin (Universiti Malaysia Sarawak (UNIMAS), 2022)
In Malaysia, there were still a few studies conducted on childhood emotional abuse and its consequences on happiness as most research would focus on psychopathological consequences, and on a few specific coping strategies such as substance use, unhealthy eating, and social supports. Childhood emotional abuse was rooted in our culture, and it went on in our daily lives whether we were aware of it or not, especially in parenting. Childhood emotional abuse was the verbal assaults on a child’s sense of worth, meanwhile, happiness was the emotion of joy, gladness, well-being. Coping strategies was defined as a series of action or thought process that was used when faced with stressful situations. This research focused to study the relationship of childhood emotional abuse on happiness level and on coping strategies. An online survey was distributed among UNIMAS undergraduate students from all of the faculties. The survey included questions from CTQ-SF, Brief-COPE, and Self-rating Happiness Scale. The correlational analysis was done by using Pearson product-moment correlation in SPSS. The results showed that there was a significant negative correlation between childhood emotional abuse and happiness level. For coping strategies, there were significant correlation between childhood emotional abuse and denial, substance use, use of emotional support, behavioural disengagement, self-blame, humour, and religion. Meanwhile, there was no significant relationship between childhood emotional abuse and self-distraction, active coping, venting, use of instrumental support, positive reframing, planning, and acceptance.